Eating disorder behaviors as a form of non-suicidal self-injury. (January 2023) - Washburn, Jason J.; Soto, Danya; Osorio, Christina A.; Slesinger, Noël C.
Highlights: Disordered eating behaviors, such as binging, purging, overexercising, or restricting food intake, may function as a form of nonsuicidal self-injury. Among patients receiving partial hospitalization or intensive outpatient treatment for nonsuicidal self-injury, nearly one-third indicate engaging in disordered eating behaviors for the purpose of causing pain or damage to their body. Patients that engage in disordered eating behaviors as a form of self-injury are more severe at the time of admission; however, they appear to benefit equally from treatment as those who self-injury but don't engage in disordered eating behaviors. Clinical services of nonsuicidal self-injury and eating disorders should consider assessing for and treating self-injurious disordered eating behaviors. Abstract: Nonsuicidal Self-Injury (NSSI), the purposeful harming of one's body tissue without suicidal intent. NSSI frequently co-occurs with other self-destructive forms of psychopathology, such as eating disorders (ED); however, it remains unclear if ED behaviors are used as a form of NSSI. This exploratory study examined the occurrence of Self-Injurious Disordered Eating Symptoms (SIDES), as well as differences in clinical correlates and treatment outcomes between NSSI patients with and without SIDES. Participants included 1, 327 patients admitted for partial hospitalization or intensive outpatient treatment for NSSI (87.4% female; 75.3% Non-Hispanic White). Data were collected at admission and discharge as part of routine clinical outcome assessment. Results indicate that 29.5% of the sample engaged in SIDES, while most were not diagnosed with an ED. Patients that engaged in SIDES reported greater clinical severity at baseline, including greater general psychopathology, lower quality of life, and worse functional impairment, as well as more clinically severe NSSI (e.g., greater number of methods, higher urge to self-injure, greater intrapersonal functions). No differences in treatment outcomes were found. These findings suggest that some NSSI patients perceive ED behaviors as a form of NSSI and that SIDES may be a marker for a more severe clinical presentation.